Mathematical Methods in Biology - Logan, J. David (John Wiley & Sons, Inc., 2015)
This textbook illustrates mathematical techniques used in many areas in the biological sciences. The last several years have witnessed a revolution in the connections between mathematics and biology. This interest in quantitative methods in biology has spawned a large number of outstanding textbooks in mathematical biology. (Many of these are included in the Reference Notes section at the end of each chapter.) This book differs from most others in that it covers both deterministic and probabilistic models. The first chapter is a long introduction and review of ideas about biological modeling, calculus, differential equations, dimensionless variables, and descriptive statistics. In the next three chapters we examine standard discrete and continuous models using difference and differential equations, and matrix algebra (there is a long appendix in Chapter 3 on matrices). The final three chapters cover probability, statistics, and stochastic processes, including bootstrap methods and stochastic differential equations.